Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11069-009-9457-1
|View full text |Cite
|
Sign up to set email alerts
|

The perceived landfall location of evacuees from Hurricane Gustav

Abstract: Hurricane evacuations in the United States are costly, chaotic, and sometimes unnecessary. Many coastal residents consider evacuation after viewing a forecasted graphic of where the storm is anticipated to make landfall. During the evacuation process, hurricane tracks commonly deviate from the forecasted landfall track and many evacuees may not pay attention to these track deviations after evacuating. Frequently, a disconnect may occur between the actual landfall track, the official forecasted track, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…In many instances during the survey process, evacuees from the greater New Orleans area stated that their experience during and immediately after Hurricane Katrina in 2005, and the impact of storm surge in particular, was a factor in determining the proper time to evacuate. Similar to the results of Senkbeil et al (2009), 83% of evacuees surveyed from the New Orleans region stated their decision to leave was influenced in part by their experience with Katrina. The impact of Katrina was less for evacuees from the Houma region, with 48% of participants stating Katrina factored into their evacuation decision.…”
Section: Storm Surgesupporting
confidence: 62%
See 3 more Smart Citations
“…In many instances during the survey process, evacuees from the greater New Orleans area stated that their experience during and immediately after Hurricane Katrina in 2005, and the impact of storm surge in particular, was a factor in determining the proper time to evacuate. Similar to the results of Senkbeil et al (2009), 83% of evacuees surveyed from the New Orleans region stated their decision to leave was influenced in part by their experience with Katrina. The impact of Katrina was less for evacuees from the Houma region, with 48% of participants stating Katrina factored into their evacuation decision.…”
Section: Storm Surgesupporting
confidence: 62%
“…Using this sampling method, evacuees stopping at each rest stop were approached at random by a member of the survey team at various locations on the grounds of the rest stop, with every effort made to ensure only one member of a vehicle or caravan of vehicles was surveyed. In addition to the questions related to the meteorological hazards of Hurricane Gustav, evacuees were asked to include additional information which was used by Senkbeil et al (2009) to assess the relationship between the perceived versus actual landfall of Hurricane Gustav. Evacuees were also asked to include their home zip code to geo-locate the survey participant's responses.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that hurricanes can cause widespread destruction, efficient evacuation strategies are critical for saving lives. Many recent studies have examined evacuation behaviors of residents in response to hurricanes (e.g., Arlikatti et al 2006;Cutter and Finch 2008;Kang et al 2007;Kusenbach et al 2010;Senkbeil et al 2010;Smith and McCarty 2009;Zhang et al 2007). These studies have shown that hurricanerelated conditions such as intensity and projected track and personal attributes (i.e., experiencing false alarms, owning pets, income, and age) affect the perceptions of risk and evacuation decisions of residents.…”
Section: Introductionmentioning
confidence: 99%